Population dynamics of the Black-headed Gull Larus ridibundus in Sweden during the last 25 years - Källander, Hans (Ornis Svecica, 1996)
Although starting its northward spread in Sweden earlier, the Black-headed Gull Larus ridibundus showed an almost explosive increase after the Second World War. However, during the last two decades the population has decreased strongly, especially in the agricultural districts of South and South Central Sweden, i.e. those areas which held the majority of the Swedish population. In this paper, data have been compiled by province from various sources (mainly papers and bird reports in local ornithological journals) in an attempt at estimating the size of this decrease and at finding any geographical pattern that might shed light on its cause, or causes. In the main agricultural areas, the decrease of the Black-headed Gull population has been in the order of 70% to 80%, on the island of Öland in the Baltic even more than 95%. Several reports indicate that the decrease started in the species' core areas in the mid-1970s when most of the large colonies diminished or disappeared, but somewhat later in less extreme agricultural areas. The reason for this recent decline is not known. Both deterioration of breeding habitat and predation by mink Mustela vison may explain a certain re-distribution of colonies from eutrophic lakes to offshore islands (and cities and industrial waste land); heavy predation by mink on gull chicks and subsequent abandonment of colonies have been reported. However, parents have abandoned chicks at colonies without documented mink predation, and chick starvation and poor fledging success have also been recorded, however most often in dry years.